THE SUITABILITY OF THE AIR BANGIS FISH LANDING BASE TO AN ECOPORT BASED PORT - Melani Analita Harianja; Jonny Zain; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThe importance of an ecoport-oriented port so that the port can prevent, process and cope with environmental pollution. This research was conducted at the Air Bangis Fish Landing Base, in order to determine the suitability of the Air Bangis Fish Landing Base to the ecoport-based port. This research was conducted in October 2020 using the survey method. The results showed that the condition of the facilities at the Air Bangis Fish Landing Base was well maintained but there were some facilities that were not available such as licensing and monitoring of fish by observers. So getting an ecoport index score of 1.77 which means that there is a need for an increase to get to the ecoport port.Keywords: PPI Air Bangis, Ecoport, Port Facility.